Pendugaan Permintaan Impor Komoditi Kedele dan Gandum Indonesia - Muchjidin Rachmat; nFN Erwidodo (Jurnal Agro Ekonomi, 1994)
Soybean and wheat imported by Indonesian government increase steadily in line with its population and welfare growth. The main reason of remarkable increasing demand is the increasing trend of the industries using those commodities as a raw material. The main source of soybean importation is China and USA, on the other hand wheat is mainly imported from Australia, USA, Canada and Argentina in determining the import demand, the AID model and translog functional form are used, but the Armington model is not suggested due to the restricted assumption needed. The result indicated that there is substitution effect for Indonesian soybean import between Asian and non-Asian Countries. For the same commodity, among Asian countries the nature of importation is complement. For wheat there is a tendency that the nature of relationship is substitute among the countries as a source of Indonesia's importation. Soybean import price elasticity ranges between -0.6 to -2.2, and -0.3 to -0.7 for wheat